2020
DOI: 10.1002/ep.13440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commercial biochar in South Korea for environmental application and carbon sequestration

Abstract: The performance of commercial wood chip (WC) and biosolid (BS) biochars available in bulk from carbonization processes in South Korea was examined via determination of sorption capacity from batch experiments and evaluation of carbon sequestration using biochar-mortar composites according to construction and environmental properties. Compared with rice straw (RS) biochar synthesized in a laboratory, the sorption capacities of WC and BC biochars are determined by the types of contaminants, the properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…563 Biochar in concrete can also be helpful to combat sick building syndrome (SBS) by removing benzene and toluene from the environment, regardless of the type of biochar employed, as shown in a recent work conducted in South Korea. 564 In the conditions of the referred work, the addition of up to 10% of biochar in concrete was able to remove 40% of toluene and benzene from the atmosphere. Additional work also assessed the possible toxicity of concrete−biochar composites by conducting TCLP (toxicity characteristic leaching procedure) tests and showed that there is no risk of harmful effects on living creatures in indoor environments.…”
Section: So (Gas)mentioning
confidence: 94%
See 3 more Smart Citations
“…563 Biochar in concrete can also be helpful to combat sick building syndrome (SBS) by removing benzene and toluene from the environment, regardless of the type of biochar employed, as shown in a recent work conducted in South Korea. 564 In the conditions of the referred work, the addition of up to 10% of biochar in concrete was able to remove 40% of toluene and benzene from the atmosphere. Additional work also assessed the possible toxicity of concrete−biochar composites by conducting TCLP (toxicity characteristic leaching procedure) tests and showed that there is no risk of harmful effects on living creatures in indoor environments.…”
Section: So (Gas)mentioning
confidence: 94%
“…Additional work also assessed the possible toxicity of concrete−biochar composites by conducting TCLP (toxicity characteristic leaching procedure) tests and showed that there is no risk of harmful effects on living creatures in indoor environments. 564 However, further work should assess the performance of lower biochar percentages since, as mentioned earlier, in civil engineering constructions, biochar content is added up to around 3% and seldom up to 5%. 562 The necessity of looking for pathways for C storage in cementitious composites (e.g., concrete) is justified by the necessity of making the cement industry more sustainable from an environmental viewpoint.…”
Section: So (Gas)mentioning
confidence: 99%
See 2 more Smart Citations
“…), abundant microchannels and stable aromatic chemical structure (such as alkaline pH and rich organic functional groups) 4 , biochar has been widely used as an environmentally friendly amendment for the treatment of wastewater and soil pollution 5 . For example, wood chip biochar (3–5%, wt) had a high ability to remove 2,4‐dinitrotoluene (DNT) and 2,4‐dichlorophenol (DCP) from an aqueous solution 6 .…”
Section: Introductionmentioning
confidence: 99%